Nrimo Ing Pandum philosophy through reality counseling approach in enhancing students' self-acceptance - Budiyono, Alief Laili; Maizura, Nining; Lismaini, Lismaini; Reidana, Linka Latifany Falasifa; Putra, Ade Herdian (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2024)
Low self-acceptance can hinder personal development and disrupt social relationships. This study aims to develop a counseling model rooted in the philosophy of nrimo ing pandum, emphasizing patience, sincerity, and self-acceptance as central tenets. A literature review methodology encompassed five key stages: literature collection, literature selection, analysis of selected works, synthesis of findings, and discussion of results. The findings highlight the integration of the nrimo ing pandum philosophy into reality counseling as a meaningful approach to fostering self-acceptance. This philosophy reflects the Javanese cultural values of resilience, commitment, morality, and acceptance. Specifically, it can be applied during the evaluation stage of counseling, enabling counselors to explore and address clients' needs and aspirations. The study concludes that integrating the nrimo ing pandum philosophy with reality counseling offers a culturally grounded alternative to enhance students' self-acceptance. These findings contribute to theoretical advancements in counseling practices by incorporating local wisdom as a foundation for effective intervention strategies.